Narrativas en el umbral: figuraciones del horror y desvíos del policial en la narrativa Argentina actual (2010-2021) (Revista de Crítica Literaria Latinoamericana, 2025)
From the denomination of “narratives on the threshold” it was sought to respond to what are the elements of the textuality that account for the figurations of horror. On the other hand, starting from the affirmation that uses and deviations of the police genre are read in the contemporary Argentine narrative, it was necessary to specify how the figurations of horror participate. The reading map was drawn from the Argentine narrative published in recent years and is constituted by the novels Polígono Buenos Aires (2013) by Marcos Herrera, Berazachussets (2013) and Medianera (2011) by Leandro Avalos Blacha, La tension del umbral (2015) and Desarmadero (2022), by Eugenia Almeida.
Keywords: Narrativas; Figuraciones del horror; Terror; Gótico; Género policial